Cervical HPV in central China: regional prevalence, subtypes and pathology - Guan, Jin; Liu, Hongliu; LI, Jilan; Chang, Zhuolin; Zhang, Mingtao; Xiao, Xuan (The Journal of Infection in Developing Countries, 2026)
Introduction: This study investigated the epidemiological characteristics, subtype distribution, and clinical correlations of cervical human papillomavirus (HPV) infection in Jingmen, China. Methodology: A retrospective study of 5,155 women screened at Jingmen Central Hospital (2022–2024). The participants were categorized into 6 age groups: ≤ 20 years (n = 54), 21-30 years (n = 791), 31-40 years (n = 1,757), 41-50 years (n = 1,371), 51-60 years (n = 968), and ≥ 61 years (n = 214). HPV genotyping and histopathology were used to assess infection patterns and lesion correlations. Results The infection rates of high-risk HPV (HR-HPV), low-risk HPV (LR-HPV), and mixed infections were 18.10% (933/5,155), 3.38% (174/5,155), and 3.38% (174/5,155), respectively. HR-HPV infections exhibited a bimodal age distribution, with peak prevalence in women aged ≤ 20 years (33.33%) and ≥ 61 years (39.25%). This age-related difference was statistically significant (χ² = 81.430, p < 0.001). The dominant subtypes were HPV52 (23.5%), HPV16 (13.9%), and HPV58 (13.3%). Notably, HPV16 was significantly more prevalent in high-grade squamous intraepithelial lesions (HSIL; 44.3%) and cervical cancer (CC; 55.5%), compared with low-grade lesions (p < 0.01). Conclusions: This study identified both adolescent/young women (≤ 20 years) and older women (≥ 61 years) as high-risk populations for HR-HPV infection. Notably, HPV16 (55.5%) exhibited significantly higher detection rates in cervical cancer cases, emphasizing the importance of prioritizing this subtype in region-specific vaccine-based prevention strategies. These findings underscore the need for tailored clinical management approaches based on viral subtype distribution and lesion severity.